Urbanidade e vitalidade nos espaços públicos em novas áreas residenciais verticalizadas: estudo de casos em Londrina - PR e Ribeirão Preto - SP - Esteves, Juliana Cardoso (Universidade Federal de São Carlos, 2022)
The projects of residential condominiums aimed at the middle and upper classes tend to privilege the interior of the building and the design of its facades, but few consider its relationship and integration with the public space and the people who use it, who have also not received due attention. of urban managers, since the adaptation of the city to the car absorbed a large part of the investments. This work aimed to analyze how the configuration of the built environment, through its morphological elements, architectural typologies, and socio-spatial practices, interferes with the vitality and urbanity of cities, especially public spaces in vertical areas. The research method adopted was the study of multiple cases in recently verticalized areas in medium-sized cities and took place in three phases: development of research instruments (observation sheets, questionnaires, interviews, thematic maps) and analysis criteria, based on the studied literature; data collection in the cities of Londrina – PR and Ribeirão Preto – SP and systematization and analysis of the data collected. To verify the main attributes of vitality and urbanity in the spaces studied, two dimensions of analysis were adopted: physical, in which questions of urban form were evaluated, and social, in which the relationship between the user and the urban space was verified. From the literature point of view, the thesis contributes to the articulation of the concepts of urbanity and urban vitality. The analysis of data and research results showed that urban form plays an essential role in the development of vitality and urbanity in public spaces in cities, as they directly interfere in the use of spaces and in the perception of users. However, this is directly linked to the experiences, specific needs, and cultural identities of each one. The case studies demonstrated the central hypothesis of the research: the same vertical typology, arranged in the urban site with different spatial arrangements, generate different urban qualities, with repercussions on aesthetic, spatial, mobility and safety perception, creating public spaces with different vitality and urbanity.
Urbanity and vitality in public spaces in new verticalized residential areas: case studies in Londrina - PR and Ribeirão Preto - SP
Urbanidad y vitalidad en espacios públicos en nuevas áreas residenciales verticalizadas: estudios de caso en Londrina - PR y Ribeirão Preto - SP
Keywords: Desenho urbano; Cidade; Praças e parques; Verticalização; Vitalidade urbana; Planejamento urbano; Urban design; Cities; Urban squares and parks; Verticalization; Urban vitality; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL; ENGENHARIAS; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO::PAISAGISMO::PROJETOS DE ESPACOS LIVRES URBANOS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::FUNDAMENTOS DO PLANEJAMENTO URBANO E REGIONAL